Zakat Payment by Metal Backed Cryptocurrencies: Are They Allowed? - Yunita, Patria (Muslim Business and Economics Review, 2022)
This study aims to provide a scientific contribution to the feasibility of metal backed cryptocurrencies as a medium of exchange to pay zakat. To understand the dynamics and mechanisms of metal backed cryptocurrencies, the autoregressive conditional heteroscedasticity and generalized conditional heteroscedasticity (Arch Garch) methods were used. The metal backed cryptocurrencies used for this research are Bitcoin Gold, GoldFinch, Gold Coin, Digix Gold Token, E-Dinar Coin, Gold-Money, and E-Gold. Our analysis finds that even though these are metal backed cryptocurrencies, the volatility is high. Gold-Money has a long-term volatility 67 times higher than the volatility of gold, while E-Gold has eight times the volatility of gold. As a result, due to high levels of volatility, metal backed cryptocurrencies are not suitable as a medium for zakat payment.